Comparison between two ceramic veneer materials in their color and translucency before and after applying luting agent layer - Bubteina, Najat H.; Mohamed, Rafa A.; Mohamed , Saied H. (Libyan Journal of Science &Technology, 2022)
Statement of problem: In making veneer restoration to restore the human teeth, it is essential to produce the color and the shape of the artificial restoration similar to the natural teeth and this is not easy produced. Therefore, the effect of cementation layer on optical characteristic of aesthetic restoration is one of the critical factors in controlling the aesthetic outcome of veneer restorations. The aim: The aim of this work is to evaluate the effect of luting cement on color and translucency of commercially available aesthetically ceramic veneer materials. Materials and methods: The materials used were Zirkon Zahn and IPS e.Max Empress. All the experimental samples of laminate veneers (LVs) were prepared using readymade veneer mould (3M ESPE) to standardize the thickness and the dimension of the tested samples. Single layer of the luting cement was applied on the fitting surface of the veneer samples. The samples prepared following the manufacturers’ instructions. Spectrophotometer was used to evaluate the color and translucency of tested samples. Results: The IPS e.max samples showed higher TP and Cab values compared with zirconia samples. However, color difference (∆E) values were higher for zirconia (3.28) compared with IPS e.max samples (2.92). Cement layer showed great effect on translucency and color parameter. Statistically, there was a high significant difference between tested samples (P>0.000) Conclusion: The IPS e.max ceramic showed better color measurement than zirconia samples, however both materials found to be in the acceptable range of observation values. The luting cement had limiting the translucency and affects the aesthetic outcome.